Creative Holobionts: Conrad Waddington and the Intra-Action of Science, Art and Philosophy - Sandberg, Ole Martin (The Nordic Journal of Aesthetics, 2025)
This article takes the work and life of Conrad Waddington to illustrate the point that science, art and humanities can be mutually constituting fields that each bring light to aspects of reality that the others may not yet have the tools or the language for and that they can thereby work together to bring new revelations and progress. Borrowing a term from Lynn Margulis, I call this interaction a Creative Holobiont. The article puts Waddington’s work on the development of organisms in the context of metaphysical questions of change and difference and describes his inspiration from the philosopher Alfred North Whitehead. It then moves on to touch upon later discoveries in biology which take us beyond the individual organism to a fully relational view of life. Finally, it discusses how this view has been represented in artistic works recently and in the past.